Design of Mathematical Proof-Based Logarithm Teaching Materials - Hamidah, Ida; Susilawati, Susilawati; Rahmasari, Shafira Meiria; Khalim, Abdul (EDUPEDIA Publisher, 2024)
The purpose of this research is to design logarithmic teaching materials based on mathematical proof. The subjects in this study were 23 students of SMA 1 Sumberjaya, Majalengka Regency, Indonesia, consisting of 23 students in class X IPA-2. This research is a pre-research of the 4P development design study adapted from the Thiagarajan model, et al. namely: (1) Definition; (2) Design; (3) Development; and (4) deployment. In this study, the stages carried out are limited to stage 3, namely development. The deployment phase will be carried out again later. The method used in this study is qualitative method with several data collection techniques in the form of tests of students' mathematical proving abilities in logarithmic material, interviews, and teaching material validation questionnaires. Based on the results of the study, it showed that teaching materials were in the appropriate category with a very good predicate with a percentage of 88.93% from material experts and in the appropriate category with a good predicate of 85.08% from media experts. The results of the practicality test on students amounted to 82.5% indicating that the teaching materials that have been made have a practicality category with a good predicate.